Antiobesity effects of resveratrol: which tissues are involved?. Issue 1 (10th August 2017) - Fernández‐Quintela, Alfredo; Milton‐Laskibar, Iñaki; González, Marcela; Portillo, Maria P.
Abstract: The prevalence of obesity has been increasing in recent decades and is reaching epidemic proportions. The current options for overweight and obesity management are energy restriction and physical activity. However, compliance with these treatments is frequently poor and less successful than expected. Therefore, the scientific community is interested in active biomolecules, which may be useful in body weight management. Among them, resveratrol (3, 5, 4′‐trihydroxy‐ trans ‐stilbene) has generated great interest as an antiobesity agent. The focus of this report is the mechanisms of action of resveratrol on several tissues (i.e., white and brown adipose tissues, liver, and skeletal muscle). Resveratrol blunts fat accumulation through decreasing adipogenesis and/or de novo lipogenesis in white adipose tissue. The effects on lipolysis are controversial. Regarding brown adipose tissue, resveratrol increases the capacity for adaptive thermogenesis. As far as liver and skeletal muscle is concerned, resveratrol increases lipid oxidation in both tissues. Therefore, in rodents, there is a general consensus concerning the effect of resveratrol on reducing body fat accumulation. By contrast, in humans, the studies are scarce, and no clear antiobesity action has been revealed so far.